2020
DOI: 10.1002/solr.202000308
|View full text |Cite
|
Sign up to set email alerts
|

Toward Efficient and Stable Perovskite Solar Cells: Choosing Appropriate Passivator to Specific Defects

Abstract: Figure 3. The impact of MABr treatment on the scanning electron microscopy (SEM) images of film morphology (MAPbI 3 films a) without and b) with MABr treatment), c) ultraviolet-visible (UV-vis) absorption spectra, and d) XRD patterns of the perovskite films. Reproduced with permission. [61] Copyright 2016, Springer Nature. e) Schematic illustration and f) SEM images of the molecule-passivated RP/3D heterostructure. Reproduced with permission. [115] Copyright 2018, Royal Society of Chemistry. g) Schematic repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 170 publications
(253 reference statements)
1
33
0
Order By: Relevance
“…Such shallow defects hence contribute to overall carrier concentrations instead of deep‐level nonradiative intraband trap states. [ 45 ] Generally, radiative band edge defects are expected to form at very high concentrations; although beneficial for light‐emitting diodes (LEDs), it is highly undesirable for solar cell applications. Defect‐tolerant studies in other systems such as transition metal dichalcogenides and other semiconductors, as shown in Figure a,b, indicate that the tendency of a material to form defect states within the bandgap is primarily influenced by the similarity of orbital characters near the conduction and valence bands of semiconductors with antibonding valence band.…”
Section: Defects In Hybrid Halide Perovskites: An Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Such shallow defects hence contribute to overall carrier concentrations instead of deep‐level nonradiative intraband trap states. [ 45 ] Generally, radiative band edge defects are expected to form at very high concentrations; although beneficial for light‐emitting diodes (LEDs), it is highly undesirable for solar cell applications. Defect‐tolerant studies in other systems such as transition metal dichalcogenides and other semiconductors, as shown in Figure a,b, indicate that the tendency of a material to form defect states within the bandgap is primarily influenced by the similarity of orbital characters near the conduction and valence bands of semiconductors with antibonding valence band.…”
Section: Defects In Hybrid Halide Perovskites: An Overviewmentioning
confidence: 99%
“…[ 44 ] Furthermore, DFT studies with different halide anions and monovalent cations confirmed that the defect landscape in these hybrid halide perovskites varies with composition; different perovskites have different dominant defects depending on their formation energy and balance among the possible existing defects. [ 45 ]…”
Section: Defects In Hybrid Halide Perovskites: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations